Books, people, and military thought : Machiavelli's Art of War and the fortune of the militia in sixteenth-century Florence and Europe - Guidi, Andrea (Thinking in extremes, 2020)
"How did the evolution of new gunpowder weapons change the nature, structure and composition of the Florentine militias during the first decades of the sixteenth century? Via an examination of little-known and unpublished sources, this book provides a comparative exploration of two Florentine republican experiments with a peasant militia: one promoted and created by Niccolò Machiavelli (1506-12) and a later one (1527-30). Using this comparison as the basis for a new reading of Machiavelli's Art of War (which drew on the author's experience with the militia), the book then investigates the relationship between the circulation and reception of Machiavelli's influential work, changing conceptions of militia, and the formation of new cultures of warfare in Europe in the sixteenth century."--